(untitled) (Environment & Health, 2024)
The purpose of the research: development and development of a new effective method of decontamination of radiation-contaminated soils to reduce the negative impact of radionuclides on the environment and human health. Research materials and methods: The research object is sandy soil contaminated with radiocesium. Research methods are applied - X-ray diffractometry, dispersion analysis, gamma spectrometry. Results: a complex method for cleaning of radioactively contaminated soil is proposed, which combines plasma-chemical treatment of the «soil – water» suspension with subsequent separation of the cleaned soil and coagulation-sorption cleaning of the formed supernatant. The supernatant contains a dispersion in the aqueous phase of micro- and nanoparticles that contain radioactive substances. The principle of heterocoagulation was used for the deposition of the solid phase, which reduces the migration of radioactive particles into the dispersion medium, using a positively charged colloid of iron hydroxide (III) as a coagulant. For deactivation of the liquid phase of the supernatant, a complex sorbent based on iron hydroxide micro- and nanoparticles modified with nickel-potassium ferrocyanides and highly dispersed layered aluminosilicates was used. At the same time, the degree of decontamination of the soil is 91.6%, and that of the supernatant is ≈98%. This method allows to get purified soil that can be used in soil reclamation processes, as well as purified water. Multiple use of process water is envisaged, which prevents additional contamination of the environment with radioactive substances. Radioactive sludge is suitable for compaction and further storage in radioactive waste storage facilities. Conclusions: Based on the results of this study, a new effective method of soil decontamination was developed and worked out, which is an effective and promising approach in combating the consequences of accidents at nuclear power plants and other sources of radiation pollution. It allows to effectively remove radioactive substances from soil and water, reducing the negative impact on the environment and human health. The main advantages of the method are its high efficiency, the possibility of reusing process water, as well as reducing the amount of radioactive waste that requires further treatment and storage. The proposed approach is an important step in preserving ecosystems and ensuring the safety of life and health of the population.